2013
DOI: 10.3109/14767058.2013.811226
|View full text |Cite
|
Sign up to set email alerts
|

Uterine incision-to-delivery interval and perinatal outcomes in transverse versus vertical incisions in preterm cesarean deliveries

Abstract: We observed no difference in Uterine Incision-to-Delivery interval and neonatal complications between vertical and transverse incision. Performance of a vertical uterine incision for the sole reason of facilitating a more rapid delivery is not justified. Development of methods to better determine transverse incision feasibility may facilitate a decrease in vertical uterine incisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 9 publications
1
11
2
Order By: Relevance
“…Also in our study there were no cases of fetal injury in any of the studied groups. This finding is in accordance with Luthra [14] in their retrospective cohort study of singleton cesarean deliveries from 2002 to 2009, they observed no difference in neonatal complications between vertical and transverse incision. However in contrary to our results Alexander et al [15] in a prospective cohort study conducted in 13 university hospitals to describe the fetal outcome in women undergoing CS.…”
Section: Inverted "T" Incision Restricted To Lower Uterine Segment Assupporting
confidence: 90%
“…Also in our study there were no cases of fetal injury in any of the studied groups. This finding is in accordance with Luthra [14] in their retrospective cohort study of singleton cesarean deliveries from 2002 to 2009, they observed no difference in neonatal complications between vertical and transverse incision. However in contrary to our results Alexander et al [15] in a prospective cohort study conducted in 13 university hospitals to describe the fetal outcome in women undergoing CS.…”
Section: Inverted "T" Incision Restricted To Lower Uterine Segment Assupporting
confidence: 90%
“…Prior studies have found increased risks of postpartum hemorrhage and blood transfusion in women undergoing classical cesarean delivery, 6, 7, 9, 10 although other studies did not find an increased risk. 4, 8 This conflicting data might be due to different inclusion criteria (term versus preterm).…”
Section: Commentmentioning
confidence: 88%
“…In a previous study, classical cesarean delivery was not associated with improved short-term neonatal outcomes compared with low transverse cesarean delivery. 10 In the long-term, it is well known that classical cesarean delivery is associated with an increased risk of uterine rupture and uterine scar dehiscence compared with low transverse cesarean delivery. 8, 14, 15 Also subsequent pregnancies require cesarean delivery at late preterm or early term due to the risk of scar dehiscence, which raises concern for abnormal placental implantation and neonatal respiratory complications.…”
Section: Commentmentioning
confidence: 99%
“…found an increased odds of blood transfusion in 187 CCD compared with 586 LTCD (OR=2.17, 95% CI 1.0–4.67). 9 Patterson et al in a 19-year review of all cesarean deliveries in the Nova Scotia Atlee Provincial Database (1980–1998) found that puerperal infection, blood transfusion, hysterectomy, intensive care unit admission, death) were each significantly higher in 221 CCD compared with 19,422 LTCD. However, the mean gestational age at delivery was significantly higher in the LTCD group (38.8 weeks of gestation) than the CCD group (31.6 weeks of gestation).…”
Section: Commentmentioning
confidence: 99%
“…610 Several mostly small studies have evaluated the relationship of preterm delivery (including variation across gestational age) and route of delivery to postpartum maternal morbidity. 5,8,9,11 The data comparing postoperative morbidity in classical versus low segment cesarean delivery in the early preterm period are also extremely limited. 5,8,9,11 The objectives of this analysis were to determine the prevalence of serious maternal complications associated with early preterm delivery by gestational age (GA) and to determine rates of serious maternal complications by route of delivery (vaginal delivery (VD); classical cesarean delivery (CCD), low transverse cesarean delivery (LTCD) and low vertical cesarean delivery (LVCD) by using highly detailed data obtained by chart abstraction by trained research personnel.…”
Section: Introductionmentioning
confidence: 99%